Sustaining school partnerships: the context of cross‐sectoral collaboration between schools in a separate education system in Northern Ireland. Issue 2 (June 2014) - Duffy, Gavin; Gallagher, Tony
<x xml:space="preserve">Abstract</x> This study explores the current understanding of cross‐sectoral collaboration between schools in a divided society. The paper provides the context surrounding inter‐school collaboration in Northern Ireland then presents findings based on a qualitative study of five post‐primary partnerships made up of schools from the various sectors in Northern Ireland (maintained/Catholic, controlled/Protestant and integrated sectors). Participants in the study are teachers and school leaders. Evidence from this study reveals a number of things: despite a separate education system made up of different sectors, schools on an inter‐sectoral basis are willing to collaborate and those represented in this study appeared disposed to sustain partnership activities; schools recognised that collaboration and partnership while beset with a number of logistical challenges, is also beneficial for pupils and institutions. In all cases there remained evidence of sustainable collaborative practice; although some of this was more developed in some partnerships than in others. In effect this paper concludes by recognising that schools do require some level of funding to sustain partnership working but that sustainability should not be couched entirely around these terms; rather, sustainability is about creating the right conditions to allow schools to develop effective and strong partnerships. These conditions are outlined in the latter stages of this paper.